2011
DOI: 10.1186/1472-6963-11-276
|View full text |Cite
|
Sign up to set email alerts
|

Health-related rehabilitation services: assessing the global supply of and need for human resources

Abstract: BackgroundHuman resources for rehabilitation are often a neglected component of health services strengthening and health workforce development. This may be partly related to weaknesses in the available research and evidence to inform advocacy and programmatic strategies. The objective of this study was to quantitatively describe the global situation in terms of supply of and need for human resources for health-related rehabilitation services, as a basis for strategy development of the workforce in physical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
137
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(147 citation statements)
references
References 19 publications
5
137
2
3
Order By: Relevance
“…While many of the results of this project reinforce those from previous studies suggesting indicators to monitor important aspects of rehabilitation services and policy such as admission and discharge barriers to medical rehabilitation [76], multi-level barriers in access to community based rehabilitation [77], patient satisfaction [78,79], rehabilitation workforce density [80] etc., there were several new findings. Human rights indicators capturing the legal and regulatory landscape of rehabilitation services, which ranked highly in both importance and feasibility, were not mentioned in previous studies, except with reference to the ratification of human right treaties [13,81] and the recognition of disabled people's right to health in national constitutions [82].…”
Section: Discussionsupporting
confidence: 65%
“…While many of the results of this project reinforce those from previous studies suggesting indicators to monitor important aspects of rehabilitation services and policy such as admission and discharge barriers to medical rehabilitation [76], multi-level barriers in access to community based rehabilitation [77], patient satisfaction [78,79], rehabilitation workforce density [80] etc., there were several new findings. Human rights indicators capturing the legal and regulatory landscape of rehabilitation services, which ranked highly in both importance and feasibility, were not mentioned in previous studies, except with reference to the ratification of human right treaties [13,81] and the recognition of disabled people's right to health in national constitutions [82].…”
Section: Discussionsupporting
confidence: 65%
“…First, in lower income countries, where the vast majority of people with disabilities live [1, 22, 23], rehabilitation providers are unavailable or in very small numbers [1, 24, 25]. Second, existing rehabilitation services and workers concentrate in urban locations and are not accessible to numerous people with disabilities living in rural settings [22, 26, 27].…”
Section: Introductionmentioning
confidence: 99%
“…This template (in questionnaire form) and following Gupta et al (2011) was used to systematically enumerate the number of workers, the employing body, where trained, and type of services provided in each of the nine occupational categories derived from the International Standard Classification of Occupations (ISCO). Traditional and complementary medicine professionals, traditional, complementary associate professionals and community-based rehabilitation workers were added, based on the findings from the literature review.…”
Section: Pacific Rehabilitation Health Workforce Template (Prhw)mentioning
confidence: 99%
“…Sourcing accurate data is challenging as many countries do not include rehabilitation personnel in their human resources for health reports (WHO, 2009). Gupta et al (2011) reported the first international mapping, noting the highly uneven distribution of the rehabilitation workforce, with the deepest penetration in high-income countries. There is a clear gap between unmet need for rehabilitation and the requirements of the UN Convention on the Rights of Persons with Disabilities (United Nations, 2006) for equity in health care (Article 25) and access to rehabilitation and habilitation (Article 26).…”
Section: Introductionmentioning
confidence: 99%